2013
DOI: 10.1016/j.toxicon.2013.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative activity of Rhinella marina and Rhaebo guttatus venom extracts from Southern Amazon

Abstract: The venom of amphibians is a fascinating source of active substances. In view of their medical importance and aiming to explore the amazing Brazilian biodiversity, we conducted bioprospecting of antiproliferative activity in extracts of Rhinella marina and Rhaebo guttatus toads occurring in the Southern Amazon of Mato Grosso, Brazil. LC-MS and HPLC analysis of the venom extracts of R. marina revealed four bufadienolides (telocinobufagin, marinobufagin, bufalin and resibufogenin. R. guttatus venom extracts cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 42 publications
1
52
1
2
Order By: Relevance
“…In further studies, the mature peptide of cathelicidin-Bg was shown to inhibit the growth of Gram-positive but not Gramnegative bacteria and fungi. In addition, many AMPs showed anti-tumor activity as observed in previous studies (Ohsaki et al, 1992;Lee et al, 2008;Ferreira et al, 2013). In this study, we showed that cathelicidin-Bg could inhibit the proliferation of HEK293 cells but not HepG2 cells; the mechanism(s) involved should be clarified in future studies.…”
Section: Discussionsupporting
confidence: 73%
“…In further studies, the mature peptide of cathelicidin-Bg was shown to inhibit the growth of Gram-positive but not Gramnegative bacteria and fungi. In addition, many AMPs showed anti-tumor activity as observed in previous studies (Ohsaki et al, 1992;Lee et al, 2008;Ferreira et al, 2013). In this study, we showed that cathelicidin-Bg could inhibit the proliferation of HEK293 cells but not HepG2 cells; the mechanism(s) involved should be clarified in future studies.…”
Section: Discussionsupporting
confidence: 73%
“…In the 1970s, these classic approaches significantly changed with the introduction of the concept of adjuvant treatment. Intensive use of post-surgical protocols, including the combination of different chemotherapies (with different mechanisms of action) with radiotherapy and, more recently, the combination with monoclonal antibodies, has improved treatment outcomes of some types of cancers (Weinberg, 2008;Ferreira et al, 2013).…”
Section: Treatment: From Surgery To the Re-ceptormentioning
confidence: 99%
“…This is an extremely well characterized method that analyzes the ability of living cells to reduce the yellow dye 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) to a purple formazan product by a pool of cellular mitochondrial and cytosolic enzymes such as succinate dehydrogenase bound to the inner mitochondrial membrane of mammalian mitochondria. This method revolutionized cellbased drug screening by offering a high-throughput screening colorimetric assay, whereas it simplified sample processing which did not require radioisotope but it is sensitive enough for miniaturization into 96-well plate formats and have been used in the search for NCEs with antiproliferative action (Alley et al 1988, Berridge et al 1996, Gonzalez and Tarloff 2001, Santos et al 2010, Ferreira et al 2013a, Leite et al 2014.…”
Section: B-16/f-10 Cell Linementioning
confidence: 99%
“…This technique has been extensively used to assess different cell types in toxicological, environmental, antimicrobial and cytotoxic susceptibility tests. It presents higher sensibility when compared to other cytotoxicity assays, since smaller amount of cells and steps are required converting it into a suitable method to evaluate proliferation in primary cultures of normal and tumor cells from mice, rats and humans (Al-Nasiry et al 2007, Rampersad et al 2012, Schoonen et al 2012, Ferreira et al 2013a). Ascite-bearing female mice between 7 and 9 days postinoculation were sacrificed by cervical dislocation and a suspension of S180 cells was harvested from the intraperitoneal cavity under aseptic conditions.…”
Section: Primary Culture Of Sarcoma 180 Cellsmentioning
confidence: 99%
See 1 more Smart Citation